Enhancing Quranic Literacy and Religious Character through the BRUS Program in Vocational Schools - Agung Asril Putra; Ilham Qadri; M. Andhika Ramadhan; Fatmi Fauzani Duski; Rahmanita Raja; Saparia Fitriani (Ahlussunnah: Journal of Islamic Education, 2026)
This study addresses the low level of Quranic literacy among first-year vocational school students as a key challenge in strengthening religious education. To overcome this issue, a school-based program, Bina Remaja Usia Sekolah (BRUS), was implemented through collaboration with local religious authorities. This study aims to examine the implementation of the BRUS program and analyze its impact on students’ Quranic literacy and religious character. A qualitative case study approach was employed, with data collected through observations, interviews, and documentation involving teachers, religious counselors, and students. The findings reveal that the BRUS program significantly improves students’ ability to read the Quran, enhances their religious understanding, and fosters positive religious character. In addition, institutional support and continuous mentoring contribute to the effectiveness and sustainability of the program. This study highlights the role of structured religious development programs as an effective model for strengthening Quranic literacy and character formation in vocational education.